Aiki and Ido Swimming. Connections Between Swimming and Martial Arts - Wojciech J. Cynarski (Jan Długosz University in Częstochowa, 2024)
The historical connections between swimming and the art of war are unquestionable. The ability to swim is still valuable not only in the navy, which is quite obvious. Overcoming water obstacles requires the same from a soldier of the land forces, and special forces additionally teach efficient diving. During the Japanese Middle Ages, a samurai should, for a full education in martial skills (in Japanese: bugei), learn the rules of swimming in armour and with weapons (in Japanese: suei-jutsu) and acquire appropriate practical skills. Nowadays, in the practice of martial arts and combat sports, swimming is recommended as an excellent complementary sport. Are there other connections between the history, philosophy and cultural heritage of martial arts and swimming? In further analyses, concepts from the tradition of Japanese martial arts and references to several varieties of martial arts of Japanese origin will be used. The author presents here his own concepts resulting from his own experience, observations and conducted analyses.